Territorialidades, lived and senses of place in advance of the productive frontier times spaces - Comerci, María Eugenia (Centro de Historia Argentina y Americana, 2010)
In full process redshift the productive border and pop-up dispute over the use and appropriation of resources, the intervention of different social subjects in the West of La Pampa is redefining productivas-reproductivas practices crianceros farmers and, consequently, the social construction of space. Since the end of the military campaigns against agents, different indigenous societies through the exercise of power, built certain territorial representations and put into action practices tending to articulate the pampean West with the national economy. However little appreciation of this space made possible the development of certain forms of organizing socio-productive and symbolic autonomy. Before the expansion of the livestock border, the imposed hydrocarbon region and increasing presence of new territorial logics grow confrontations by unequal access to natural resources, the appropriation of space and the construction of territorialidades. In this context, article focused on the internal organisation of rural settlements and social uses of spaces of time, in two areas of the West "end" look: La Humada and Chos Malal. This mode is intended to establish how organized spaces home, peridomestic and mount and what senses expressed subjects into life and places spaces in times of expansion of the production frontier. The new social field generated product of capitalism on the peasant drives progress is expressed, not only changes in forms of livestock, management organization of production and social construction of space, but also in forms of sociability and collective resistance strategies. This process, which is brewing in the region, has a similar development in other spaces where productive progress has occurred before or at a faster pace. Different qualitative methodology strategies that combine the study case with life stories, in-depth interviews and analysis of documentary sources are articulated for the conduct of research.